THE ABUSE AND MISUSE OF PROSECUTORIAL DISCRETION IN HIGH-PROFILE CORRUPTION CASES IN NIGERIA: A CALL FOR A PARADIGM SHIFT - Salau, Aaron (Journal of Anti-Corruption Law, 2024)
This article focuses on the place of prosecutorial discretion in the Nigerian context and asks whether and to what extent prosecutorial discretion in high-profile corruption cases involving public officials ought to be guided and constrained by the principles of impartiality, accountability and transparency. In Nigeria, the Attorney General of the Federation (and each state) has the discretion to institute, take over, and discontinue criminal prosecution against any person subject to the constitutional caution to “have regard to the public interest, the interest of justice and the need to prevent abuse of legal process” in its exercise. Despite this constitutional caution, the courts have held that the exercise of such discretion is immune from judicial review. Lately, cases involving the political class and public servants accused of extensive theft of public funds and corrupt practices have been plea-bargained with ludicrous sentences being handed down by Nigerian courts. Considering the widely held belief of political interference, bias and prejudice in these prosecutorial decisions and the damage done thereby to the rule of law, a critical reflection surrounding prosecutorial discretion in Nigeria is imperative. This article draws on doctrinal as well as comparative legal methods to argue that the available devices to constrain prosecutorial discretion in Nigeria do not go far enough to guarantee fairness and accountability and ought to be reformed. The South African model despite its limitations is associated with transparency and accountability and provides an alternative avenue for reform of prosecutorial discretion in Nigeria.